(untitled) (Proceedings OPTIMAL, 2024)
Breastfeeding can save 1.5 million babies a year from infant morbidity and mortality. Grandma’s class can have an effect on exclusive breastfeeding and MP-breastfeeding. The grandmother class program is an effort to empower the community and support stunting prevention during the golden period of toddlers. The research method used is descriptive with a cross-perspective approach. Objective: To find out the relationship between the socialization of the grandmother class and the attitude of grandmothers towards exclusive breastfeeding in Babakan Village, Sandubaya District, Mataram City in 2022. The results of the study of respondents based on age, most of the respondents were in the early elderly category, namely 18 people (60%) aged 46-55 years, 22 people with low education (73.7%) and the number of respondents who worked and did not work was the same, namely 15 people each (50%). The socialization of the grandmother class participated in the full activity as many as 24 respondents (80%). Grandma’s knowledge of exclusive breastfeeding was 28 people (93.3%). The effect of socialization of grandmother class with grandmother’s knowledge on exclusive breastfeeding was obtained from the results of statistical tests there was a significant relationship between the socialization of grandmother’s class and grandmother’s knowledge on exclusive breastfeeding with a p-value of 0.049< 0.05. Recommendation: Health workers should be able to provide support and motivation in a continuous manner to be able to achieve the success of the grandmother’s class program